2018
DOI: 10.1159/000493457
|View full text |Cite|
|
Sign up to set email alerts
|

The CircRNA-ACAP2/Hsa-miR-21-5p/ Tiam1 Regulatory Feedback Circuit Affects the Proliferation, Migration, and Invasion of Colon Cancer SW480 Cells

Abstract: Background/Aims: Circular RNAs (circRNAs), a type of RNA that is widely expressed in human cells, have essential roles in the development and progression of cancer. CircRNAs contain microRNA (miRNA) binding sites and can function as miRNA sponges to regulate gene expression by removing the inhibitory effect of an miRNA on its target gene. Methods: We used the bioinformatics software TargetScan and miRanda to predict circRNA-miRNA and miRNAi-Mrna interactions. Rate of inhibiting of proliferation was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 22 publications
2
74
0
Order By: Relevance
“…Accumulating evidence has shown that various biochemical cellular processes including proliferation and migration are under the control of circRNAs. 26 Based on the obtained results, the putative tumour suppressor function of circ-0000190 in human osteosarcoma cells was examined. Numerous assays we conducted revealed that overexpression of circ-0000190 weakened cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that various biochemical cellular processes including proliferation and migration are under the control of circRNAs. 26 Based on the obtained results, the putative tumour suppressor function of circ-0000190 in human osteosarcoma cells was examined. Numerous assays we conducted revealed that overexpression of circ-0000190 weakened cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…13 In colon cancer, circRNA-ACAP2 sponges miR-21-5p to regulate cell proliferation, migration and invasion. 14 In ovarian cancer, hsa_circ_0061140 affects cell growth and metastasis through sponging miR-370. 15 Here, we found that circEPSTI1 could bind to miR-942 and acted as a miRNA sponge.…”
Section: Discussionmentioning
confidence: 99%
“…Six circRNAs have been found to be upregulated during the progression of CRC, and knockdown of circCCDC66 [46], circRNA-ACAP2 [47], and hsa_circ_0000069 [48] notably restrained CRC cell migration, invasion, and proliferation. In addition, circ-BANP [49] and hsa_circ_0007534 [50] participate in the regulation of CRC cell proliferation.…”
Section: Circrnas That Act As Oncogenes In Crcmentioning
confidence: 99%
“…In addition, circ-BANP [49] and hsa_circ_0007534 [50] participate in the regulation of CRC cell proliferation. Among these six circRNAs, circCCDC66 [46], circRNA-ACAP2 [47], and hsa_circ_0020397 [51] could be miRNA sponges that regulate the expression level of their targets.…”
Section: Circrnas That Act As Oncogenes In Crcmentioning
confidence: 99%
See 1 more Smart Citation